2012
DOI: 10.1136/bcr-2012-006601
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder malakoplakia in type 2 diabetes mellitus: a rare entity

Abstract: Gallbladder malakoplakia in type 2 diabetes mellitus is a rare condition. Differentiating malakoplakia, which is a more aggressive disease condition with possible genetic abnormality from a more benign but closely related condition such as xanthogranulomatous cholecystitis, is of prognostic importance in postoperative patient management and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…By mimicking carcinoma gall bladder Malakoplakia has influenced treatment protocol in several previous case reports [1,2,9], like compelling frozen section as in our case or performing aggressive and extended resections. Post operatively Malakoplakia requires specific chemotherapy that concentrates in macrophages such as quinolone, trimethoprimsulfamethoxazole [2].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…By mimicking carcinoma gall bladder Malakoplakia has influenced treatment protocol in several previous case reports [1,2,9], like compelling frozen section as in our case or performing aggressive and extended resections. Post operatively Malakoplakia requires specific chemotherapy that concentrates in macrophages such as quinolone, trimethoprimsulfamethoxazole [2].…”
Section: Discussionmentioning
confidence: 78%
“…By mimicking carcinoma gall bladder Malakoplakia has influenced treatment protocol in several previous case reports [1,2,9], like compelling frozen section as in our case or performing aggressive and extended resections. Post operatively Malakoplakia requires specific chemotherapy that concentrates in macrophages such as quinolone, trimethoprimsulfamethoxazole [2]. Bethanechol, a choline agonist, has been used in Malakoplakia [10] with the concept that bethanechol may correct the decreased cGMP levels that are important for microtubular and lysosomal function in macrophages [5].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Some studies have also reported that the combination of sulfonamides or rifampicin with quinolone therapy increases the anti-infective effect. Recently, it has also been suggested that cholinergic agents such as methine choline combined with vitamin C can increase the intracellular cGMP/cAMP ratio in macrophages, thereby improving intracellular lysosomal function in macrophages, and it is effective in patients with malakoplakia ( 13 , 14 ).…”
Section: Treatmentsmentioning
confidence: 99%